2021
DOI: 10.3390/cancers13184575
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Radiobiology of Vestibular Schwannomas to Overcome Radiation Resistance

Abstract: Vestibular schwannomas (VS) are benign tumors arising from cranial nerve VIII that account for 8–10% of all intracranial tumors and are the most common tumors of the cerebellopontine angle. These tumors are typically managed with observation, radiation therapy, or microsurgical resection. Of the VS that are irradiated, there is a subset of tumors that are radioresistant and continue to grow; the mechanisms behind this phenomenon are not fully understood. In this review, the authors summarize how radiation caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 223 publications
(305 reference statements)
0
13
0
Order By: Relevance
“…When VS is treated with SRS, the goal is to maximize tumor control while minimizing toxicity to essential anatomic structures, such as the facial nerve, trigeminal nerve, and cochlea. Although retrospective investigations have shown that single fraction radiation with Gamma Knife SRS (marginal tumor dose, ~11-13 Gy) is associated with tumor control rates of 84% to 94% in VS, [12][13][14][15] facial nerve palsy occurs in approximately ~1% of patients, and progression to unserviceable hearing occurs in roughly 75% at 10 years. 10,[29][30][31][32][33] Thus, introduction of radiosensitizers such as RI-1 may improve tumor control rates and/or permit lower dosages of radiation with equivalent tumor control and less toxicity to adjacent neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When VS is treated with SRS, the goal is to maximize tumor control while minimizing toxicity to essential anatomic structures, such as the facial nerve, trigeminal nerve, and cochlea. Although retrospective investigations have shown that single fraction radiation with Gamma Knife SRS (marginal tumor dose, ~11-13 Gy) is associated with tumor control rates of 84% to 94% in VS, [12][13][14][15] facial nerve palsy occurs in approximately ~1% of patients, and progression to unserviceable hearing occurs in roughly 75% at 10 years. 10,[29][30][31][32][33] Thus, introduction of radiosensitizers such as RI-1 may improve tumor control rates and/or permit lower dosages of radiation with equivalent tumor control and less toxicity to adjacent neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms of radiation resistance of VS in patients are largely unknown but are likely related to several factors: (1) insufficient radiation dosages to initiate cell death, (2) efficient DNA repair systems, (3) tumor hypoxia preventing generation of radiation-induced reactive oxygen species, (4) altered expression of tumor suppressor and proto-oncogenes, (5) aberrant expression of cell cycle checkpoint proteins, (6) cumulative effects of the loss of function of the NF2-merlin tumor suppressor on cell proliferation, and (7) prolonged cell cycle arrest for DNA repair. 12,16,23-26 In our previous study, we showed that radioresistant VS cells mount a strong p21 response after radiation exposure (18 Gy), which can direct cells into cell cycle arrest and allow time for RAD51-associated repair of DNA damage. 21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in clinical practice, patients can develop different degrees of resistance to RT, leading to treatment failure and recurrence of metastasis, thus limiting the efficacy of RT for treatment of tumors ( Makhov et al, 2018 ). Addressing the sensitivity of RT has become a pivotal issue in the efficacy of RT in patients with tumors ( Huang and Zhou, 2020 ; Thielhelm et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%